MIMO Terahertz Quantum Key Distribution Under Restricted Eavesdropping - Neel Kanth Kundu; Matthew R. McKay; Andrea Conti; Ranjan K. Mallik; Moe Z. Win (IEEE Transactions on Quantum Engineering, 2023)
Quantum key distribution (QKD) can provide unconditional security to next-generation communication networks guaranteed by the laws of quantum physics. This article studies the secret key rate (SKR) of a continuous variable QKD (CV-QKD) system using multiple-input multiple-output (MIMO) transmission and operating at terahertz (THz) frequencies. Distinct from previous works, we consider a practical “restricted” eavesdropping scenario in which Eve can collect only a fraction of photons lost in the environment. We propose a system model for the MIMO THz CV-QKD system that accounts for restricted eavesdropping via a lossy wireless channel between Alice and Eve. We derive for this system new SKR expressions for both coherent-state-based and squeezed-state-based CV-QKD protocols. Our results show that previous analysis assuming unrestricted eavesdropping leads to overly pessimistic SKRs, and that in practice, the achievable SKR can be significantly increased under restricted eavesdropping. The increase in the SKR is quantified by the simplified SKR expansions derived in this article. Our results also reveal that squeezing is beneficial for improving the SKR only for unrestricted eavesdropping. However, in a practical setting with restricted eavesdropping, increased squeezing leads to a reduction in the SKR.